COMPARATIVE EFFICACY OF DIFFERENT THERAPEUTIC AGENTS IN EXPERIMENTALLY INDUCED LEISHMANIASIS IN HAMSTER - H. Z. Durrani; A. Z. Durrani; N. Kamal (Journal of Animal and Plant Sciences, 2010)
Two hundred sand flies were collected from the D. G. Khan and Rajanpur areas of Pakistan from May 2007 to June 2008. The species of sand flies identified were Phlebotomus. papatasi; P. orientalis; P. major. Seventy eight out of one hundred twenty flies (65%) dissected, carried the infective leptomonad forms naturally (leishmania promastigotes) in their salivary glands and fore-guts. Seven groups (A, B, C, D, E, F and G) of hamsters were experimentally infected. Out of 80 animals 78 (88%) developed characteristic lesions of cutaneous leishmaniasis at the site of subcutaneous injection. The efficacy of therapeutic agents in Group A treated with Sodium Stibogluconate solution was 90 percent, in group B Meglumine Antimonate solution was 100 percent, in group C treated with Clotrimazole 20 percent while in group D treated with Miconazole (20%) the efficacy was 100 percent . Similarly crude extracts of Garlic (Allium sativa) was applied on lesions to group-E; thrice a day which cured the lesions within 60 days; Onion (Allium cepa) (T-6) were applied on the lesions of group-F; TDS; which cured the lesions within 72 days and Harmal extracts (T-7) were applied on lesions to group-G; TDS; this cured the lesions within 50 days, respectively.
Keywords: Leishmania; phlebotomus; hamster; herbal agents